Does the presence of Oil and gas infrastructure potentially increase risk of harvest in northern bobwhite?. Issue 6 (1st November 2016) - Tanner, Evan P.; Elmore, R. Dwayne; Davis, Craig A.; Fuhlendorf, Samuel D.; Dahlgren, David K.; Thacker, Eric T.; Orange, Jeremy P.
Abstract : Beyond organisms experiencing direct impacts (mortality) from the presence of anthropogenic features, interactive relationships may exacerbate the effects of anthropogenic disturbance within the context of these features. For example, mortality risk may be affected by the road infrastructure associated with energy development by influencing space use of predators including human hunters. To assess these relationships, we conducted research on northern bobwhite Colinus virginianus across a hunted and non‐hunted area of Beaver River Wildlife Management Area, Oklahoma, using radiotelemetry from 2012–2015. We found that bobwhite mortality risk decreased as the distance from primary roads (m) increased across weeks (hazard ratio [HR] = 1.008, 95% confidence interval [CI] = 1.0003 to 1.0013). The interaction between unit (hunted and non‐hunted) and distance from primary roads was not significant (HR = 1.00, 95% CI = 0.999 to 1.001) indicating that hunting pressure was not a likely explanation for the observed decrease in survival related to primary roads. Bobwhite on the hunted unit avoided exposed soil/sparse vegetation ( = ‐0.01, CI = ‐0.02 to ‐0.002) and bare ground ( =‐0.01, CI =‐0.02 to ‐0.002) more than bobwhite on the non‐hunted unit, however these were weak relationships. No other differences in bobwhite space use were detected related to hunting. Though we were limited to estimating theoretical rather than empirical amounts of hunting pressure during our study, we were unable to detect any negative compounding effects of anthropogenic development and hunting pressure on bobwhite ecology during the hunting season.